Estudo da otimização do processo de usinagem da superliga de níquel 80A por torneamento - Lopes, Carolina Silva de Faria [UNESP] (2013)
The search for materials with higher properties and characteristics (wear resistance, oxidation, corrosion, etc.) has driven research of various materials. Among the materials that are being studied with such properties and characteristics are super alloys based on nickel which has an important role in the aeronautical, automotive, marine, production of gas turbines and now in space vehicles, rocket engineering, experimental aircraft, nuclear reactors, steam-powered plants, petrochemical and many other applications because besides having all the characteristics and properties mentioned above also have an excellent performance at high temperatures. The super alloy based on nickel studied in this work is the super alloy Nimonic 80Anormally used in the manufacture of exhaust valves in common engines and diesel engines of high power by cater requirements such as mechanical strength and corrosion resistance at temperatures of approximately 815 ° C. The objective of this work is to produce results to demonstrate more specific information about the real influence of coatings on cutting tools and cutting fluids in turning and thus promote the optimization of the machining of these alloys. The super alloy Nimonic 80Aused went through turning, being this performed with various machining parameters such as cutting speed, feed rate, depth in conditions of Minimum Amount of Fluid (MAF), abundant fluid, cutting tools with coating and without coating in early in his work life and with wear. After turning were obtained several samples of chips and the part generated during the machining process, was measured roughness of the material, subsequently made macrostructural analysis of the tools used order to detect possible wear and microstructural analysis of samples collected being that the latter was used for Optical Microscopy and Energy Dispersive ...(Complete abstrac click electonic access below)